Structural modification on potato tissue and starch using ethanol pre-treatment and drying process - Guedes J.S. (2021)
The authors are grateful to the Sao Paulo Research Foundation (FAPESP, Brazil) for funding the project n? 2019/05043-6; this study was financed in part by the ?Coordena??o de Aperfei?oamento de Pessoal de N?vel Superior - Brazil (CAPES)? ? for the JS Guedes (88882.378356/2019-01) and KC Santos (88882.378385/2019-01) M.Sc. scholarships; to the National Council for Scientific and Technological Development (CNPq, Brazil) for the JS Guedes M.Sc. scholarship (131235/2020-6) and the productivity grant of PED Augusto (306557/2017-7); and to the Fondo Nacional de Desarrollo Científico, Tecnológico y de Innovación Tecnológica (FONDECYT, Peru) from the ?Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica? (CONCYTEC, Peru) for funding the project n° 409-2019-FONDECYT.